2020
DOI: 10.1021/acs.jpclett.0c02203
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the Interaction between the Spike Protein of Severe Acute Respiratory Syndrome Coronavirus-2 and the Receptor of Human Angiotensin-Converting Enzyme 2. Effects of Possible Ligands

Abstract: Since the end of 2019, the coronavirus SARS-CoV-2 has caused more than 1000000 deaths all over the world and still lacks a medical treatment despite the attention of the whole scientific community. Human angiotensin-converting enzyme 2 (ACE2) was recently recognized as the transmembrane protein that serves as the point of entry of SARS-CoV-2 into cells, thus constituting the first biomolecular event leading to COVID-19 disease. Here, by means of a state-of-the-art computational approach, we propose a rational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 64 publications
1
39
0
Order By: Relevance
“…In our previous in silico study, we searched for the most druggable binding site on RBD of S-glycoprotein for testing the PoPEx potential for interaction. However, interactions with any of RBD amino-acid residues could potentially interfere with S-glycoprotein and ACE2 receptor contacts [22] . Therefore, in this study, we expanded our docking simulation to the whole S-glycoprotein RBD region and introduced the molecular dynamic simulation to test the ligand-protein dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous in silico study, we searched for the most druggable binding site on RBD of S-glycoprotein for testing the PoPEx potential for interaction. However, interactions with any of RBD amino-acid residues could potentially interfere with S-glycoprotein and ACE2 receptor contacts [22] . Therefore, in this study, we expanded our docking simulation to the whole S-glycoprotein RBD region and introduced the molecular dynamic simulation to test the ligand-protein dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several reports have demonstrated that the spike protein is important for the viral life cycle and it is an important target to block viral cell entry. 1,4,15 Currently, computational works have reported peptides and small molecules as inhibitors of the spike RBD. 1,4,[15][16][17][18] However, to the best of our knowledge, there is no study which has reported the antiviral effectiveness of neem extracts as spike RBD-ACE2 inhibitors in silico.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the structure [20,21] and the function [22] of spike protein and possible blockers [23][24][25][26] to target and suppress the virus through its spike protein. For instance, Han and Kral [27] designed peptide inhibitors with α-helix structure against spike protein.…”
Section: Introductionmentioning
confidence: 99%